Program Penyemaian Benih Cabai dalam Polybag: Budidaya Praktis dan Ekonomis - Andini Okta Nurusama Wati; Lilis Sugita; Ega Wahyuni; Adinda Amalia; Tessa Tessa; Dinda Lestari; Armadi Syahbani; Sulastio Sulastio; Aldi Saputra; Alfi Syahri Mubarak (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Real Work Lecture (KKN) is a form of student service to the community through empowerment programs. In KKN activities in Munggu Village, Sungai Selan District, Central Bangka Regency, the KKN team carried out the program